Regional Integration as a Strategic Avenue for Bangladesh LDC Graduation with Momentum - United Nations Conference on Trade; Development (United Nations, 2023)
The report outlines the state of Bangladesh’s economy in the wake of COVID-19, and the likely impacts of the phasing out of LDC-specific international support measures upon LDC graduation. The study then analyzes the strategic rationale for strengthening Bangladesh’s regional integration as a way to (i) mitigate the adverse impacts of the phasing out of LDC-specific preferential market access; and (ii) foster the diversification of the economy and a more conducive participation in regional value chains.